Visualization of Thrombosis on a Prosthetic Pulmonary Valve Using Electrocardiogram-Gated Multidetector Computed Tomography - Kakizaki, Shuhei; Tazawa, Seiichi; Kure, Shigeo; Saiki, Yoshikatsu (The Thoracic and Cardiovascular Surgeon Reports, 2014)
We report a case of prosthetic valve thrombosis in an 18-year-old man. Total surgical repair of tetralogy of Fallot was performed at 3 years of age. At the age of 18, he underwent pulmonary valve replacement because of exacerbating pulmonary trunk obstruction. After surgery, valve malfunction was suspected. We attempted to employ electrocardiogram (ECG)-gated multidetector computed tomography (MDCT). The stuck valve was clearly visualized together with a thrombus within. Thrombolytic therapy was undertaken on these findings. ECG-gated MDCT allowed us to make a definitive diagnosis of valve thrombosis as the cause of valve malfunction, which led us to avoid surgical reintervention.
Keywords: stuck valve; computed tomography; thrombolysis